Thrombosis of the cavernous sinus secondary to Aspergillus spp. - Pamo-Reyna, Oscar G. (2019)
A 39 year-old woman with severe neutropenia due to bone marrow hypoplasia and ethmoidal and sphenoidal sinusitis by Aspergillus spp. developed a right cavernous sinus thrombosis. The patient died despite of the treatment with amphotericin B.